Usefulness of intellectual capital information: preparers' and users' views - Abdulrahman Anam , Ousama; Abdul Hamid, Fatima; Abdul Rashid, Hafiz Majdi (Emerald Group Publishing Limited, 2011)
This paper aims to investigate preparers’ and users’ perceptions on the usefulness of intellectual capital (IC) information disclosed in annual reports of listed companies. In addition, it aims to examine the significant differences in the perceptions of usefulness of IC information and IC categories of the preparers and users.